Gene expression profiles for a prognostic immunoscore in gastric cancer. Issue 10 (25th April 2018) - Zeng, D; Zhou, R; Yu, Y; Luo, Y; Zhang, J; Sun, H; Bin, J; Liao, Y; Rao, J; Zhang, Y; Liao, W
Abstract: Background: Increasing evidence has indicated an association between immune infiltration in gastric cancer and clinical outcome. However, reliable prognostic signatures, based on systematic assessments of the immune landscape inferred from bulk tumour transcriptomes, have not been established. The aim was to develop an immune signature, based on the cellular composition of the immune infiltrate inferred from bulk tumour transcriptomes, to improve the prognostic predictions of gastric cancer. Methods: Twenty-two types of immune cell fraction were estimated based on large public gastric cancer cohorts from the Gene Expression Omnibus using CIBERSORT. An immunoscore based on the fraction of immune cell types was then constructed using a least absolute shrinkage and selection operator (LASSO) Cox regression model. Results: Using the LASSO model, an immunoscore was established consisting of 11 types of immune cell fraction. In the training cohort (490 patients), significant differences were found between high- and low-immunoscore groups in overall survival across and within subpopulations with an identical TNM stage. Multivariable analysis revealed that the immunoscore was an independent prognostic factor (hazard ratio 1·92, 95 per cent c.i. 1·54 to 2·40). The prognostic value of the immunoscore was also confirmed in the validation (210) and entire (700) cohorts. Conclusion: The proposed immunoscore represents a promising signature for estimating overall survival in patients with gastric cancer. Abstract : Immunoscore predicts prognosis